Implementasi Pembelajaran Sosiologi Berbasis Kearifan Lokal di Kelas XII SMAN 1 Boyolangu Tulungagung - Nadya Putri Cantika; Yudi Krisno Wicaksono (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study aims to examine the implementation of local wisdom-based Sociology learning in strengthening students' understanding of regional culture at SMAN 1 Boyolangu. A descriptive qualitative approach was used, with data collected through observation, interviews, and documentation. The research subjects were teachers and 12th-grade students. The results indicate that the learning process integrates elements of local culture into Sociology materials through discussions, cultural site visits, and local case studies. This implementation positively impacts students by increasing their learning interest, cultural understanding, and sense of pride in local heritage. Challenges include limited local-based learning resources and insufficient teacher training. These findings suggest that a local wisdom-based approach is effective in supporting contextual and meaningful learning.